Imaging phase separation in model lipid membranes through the use of BODIPY based molecular rotors1. Issue 28 (28th July 2015) - Dent, Michael R.; López-Duarte, Ismael; Dickson, Callum J.; Geoghegan, Niall D.; Cooper, Jonathan M.; Gould, Ian R.; Krams, Rob; Bull, James A.; Brooks, Nicholas J.; Kuimova, Marina K.
<x xml:space="preserve">Abstract</x> Viscosity in the phase-separated lipid bilayers is investigated through the use of fluorescence spectroscopy and molecular dynamics simulations.